Experimental research on the feasibility of phosphogypsum-enzyme induced carbonate precipitation (EICP) solidified loess - Tao Dang; Yuanzhu Ji; Yuanquan Guo; Fangchen Ma; Zhiyi Zhang; Baozhen Liang; Xuewen Rong (Scientific Reports)
Abstract To improve the effect of bio-cemented loess, taking into account the characteristics of phosphogypsum and the biochemical principle of enzyme-induced calcium precipitation (EICP), a series of mechanical and microscopic tests are designed and carried out to systematically analyze the enhancement effect of phosphogypsum enhanced EICP solidified loess and the enhancement mechanism. Concentrations of urea and calcium chloride as variables, and unconfined compressive strength (UCS) as an indicator to determine the optimal solution ratio of EICP. Subsequently, different phosphogypsum incorporation ratios were considered to determine the optimal mix proportion for EICP-phosphogypsum co-stabilized loess.The results showed that the addition of phosphogypsum can effectively improve the UCS, water stability, shear strength, and compression characteristics of EICP solidified loess. The phosphogypsum-EICP method has a better effect on improving the strength and water stability of loess with the content of phosphogypsum at 1.0%, compared with the loess treated by EICP, the strength of the specimen with 1.0% phosphogypsum content increased by 19.7%. The microstructure of the solidified loess specimens indicates that the calcium carbonate crystals generated by EICP fill the pores in the loess, thereby reducing its porosity. In addition, phosphogypsum reacts with water to produce hydration, resulting in stronger cementation between calcium carbonate and soil particles.